Cover Feature: Hierarchically Porous Co−N−C Cathode Catalyst Layers for Anion Exchange Membrane Fuel Cells (ChemSusChem 18/2019). Issue 18 (19th September 2019) - Zhang, Junfeng; Zhu, Weikang; Pei, Yabiao; Liu, Yang; Qin, Yanzhou; Zhang, Xiangwen; Wang, Qingfa; Yin, Yan; Guiver, Michael D.
Abstract : The Cover Feature shows a hierarchically porous catalyst layer based on the carbon black‐controlled synthesis of a cobalt‐based zeolitic imidazolate framework, with the aim of optimizing the triple‐phase boundary and mass transfer. The resulting catalyst layer exhibits a power density comparable to that of a commercial 60 wt. % platinum on carbon catalyst. More information can be found in the Communication by J. Zhang, W. Zhu, et al onpage 4165 in Issue 18, 2019 (DOI:10.1002/cssc.201901668 ).